PENGARUH PENGGUNAAN EDIBLE COATING PATI SAGU DENGAN PENAMBAHAN EKSTRAK DAUN KESUM TERHADAP MUTU TELUR AYAM KONSUMSI PADA PENYIMPANAN YANG BERBEDA - Murianto, Benni; Lestari, Retno Budi; Tribudi, Yuli Arif (Jurnal Sains Mahasiswa Pertanian, 2020)
Storage of chicken egg without special treatment, only up to two weeks there will be a decrease in quality. An alternative in maintain the quality of chicken egg is applied edible coating. The purpose of this research to determine effect edible coating sago starch with the additional of kesum leaf extract to qualitys egg and determine effect the interactions between the aplication edible coating sago starch with the additional of kesum leaf extract during difference stored to qualitys egg. This research used a method experiment Completely Randomized Design (CRD) factorial pattern with two factors, namely the concentrations of kesum leaf extract (K) and difference egg storages (L) consisting of concentrations namely K0 (control), K1 (edible coating + 0% kesum leaf extract), K2 (edible coating + 0,6% kesum leaf extract) and K3 (edible coating + 1,2% kesum leaf extract) and egg storage time, namely L0 (0 days), L1 (7 days), L2 (14 days), L3 (21 days), L4 (28 days) and L5 (35 days). The observed variables is egg weight loss, yolk index, albumin index and haugh unit. Results of the Analysis of Variance showed the effect edible coating sago starch with the addition of kesum leaf extract and interaction the effect edible coating sago starch with the addition of kesum leaf extract on difference storage of very significantly (P<0.01) to haugh unit with averages 63,09 – 69,59, yolk index with average 0,204 – 0,327, albumin index with averages 0,035 to 0,058. It was concluded that the use edible coating  sago starch with the addition kesum leaf  exstract of 1,2% can maintain the quality of chicken egg until storage for 21 days.